1988
DOI: 10.1073/pnas.85.12.4128
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin causes increases in expression of c-erb-A and levels of protein-tyrosine kinases in selected tissues of responsive mouse strains.

Abstract: ABSTRACT2,3,7,8,-Tetrachlorodibenzo-p-dioxin (TCDD) administered in vivo causes drastic reduction in the weight of the mouse thymus at low doses (e.g., 30 pg/kg single i.p. i jection), the reduction becoming statistically significant after 2 days. To understand the cause for such thymic involution TCDD-evoked changes in various biochemical parameters in this tissue were examined. The most noticeable change was observed in the increased activity of specific protein-tyrosine kinases and protein kinase C and an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Increases in tyrosine phosphorylation appear to be a rapid and sensitive response to dioxin exposure, both in vivo (19)(20)(21)(22) and in vitro (19,23,24). The possibility of two roles for the Ah receptor, both as a transcriptional enhancer and as a regulator of second messengers such as tyrosine phosphorylation, appears to be similar to what has been described for the steroid hormones (25,26).…”
Section: Introductionmentioning
confidence: 61%
“…Increases in tyrosine phosphorylation appear to be a rapid and sensitive response to dioxin exposure, both in vivo (19)(20)(21)(22) and in vitro (19,23,24). The possibility of two roles for the Ah receptor, both as a transcriptional enhancer and as a regulator of second messengers such as tyrosine phosphorylation, appears to be similar to what has been described for the steroid hormones (25,26).…”
Section: Introductionmentioning
confidence: 61%
“…The activation of PKs has been clearly shown to be dependent on TCDD binding to the AHR, a cytosolic, ligandactivated transcription factor of the basic helix-loop-helix type (14,15). Evidence of AHR dependence for TCDD-induced PK activation includes dose-response relationships, structure-activity relationships, the use of responsive and nonresponsive strains of animals, and the use of AHR blockers (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Polycyclic hydrocarbons such as benzo[a]pyrene, which are proven ligands for the Ah receptor, can cause mutation and tumor initiation following metabolic potentiation (60). It has been shown that TCDD stimulates kinase activities in vivo, particularly those of protein kinase C and various tyrosine kinases (5,6). An understanding of the events leading to the simultaneous activation of the protein kinase C second messenger pathway (and perhaps others) and of mammalian CYPJAl transcription may provide valuable insight into the molecular basis of Ah receptor-mediated toxicity, tumor initiation and promotion, and perturbation of growth and differentiation.…”
Section: Downloaded Frommentioning
confidence: 99%